A viewpoint of the implementation of qualitative case studies on Malay language education research naturalisation - Mohamed Mokhtar, Marzni; Jamil, Marni (AL-HAJJAJ Enterprise, 2021)
In Malay language education, two main steps to be implemented in the process of Malay language teaching and learning naturalisation process (PdP) include (i) the practice on the mastery of accurate sentence structure in accordance with the context of language use; and (ii) the involvement of students in language use activities (communication activities) planned by the teacher to enable students to use the selected structure in the context of language use. Qualitative research design is of choice among researchers in the field of Malay language because of its qualitative case study ability to make detailed descriptions of the PdP naturalisation process. Nevertheless, the perception that qualitative case study is easy to implement needs to be duly scrutinised. Qualitative case studies require the researcher’s high level of commitment that demands the role of a research instrument. Malay education research should be concerned about the needs and specific characteristics of qualitative case studies to obtain rich and meaningful research data. Thus, this paper discusses matters related to the assumption of qualitative research design selection paradigm, the specific characteristics of qualitative case studies, the process of Malay language education naturalisation, the basic implementation of qualitative case studies in the Malay language education, and the framework of qualitative case studies reporting guidelines in the Malay language education.